Medicarpin induces G1 arrest and mitochondria-mediated intrinsic apoptotic pathway in bladder cancer cells - Chen Yuan; Yin Liqi; Hao Mingxuan; Xu Wenkai; Gao Jixian; Sun Yuxin; Wang Qiao; Chen Shi; Liang Youfeng; Guo Rui; Zhang Jinku; Li Jinmei; et al. (Acta Pharmaceutica)
Bladder cancer (BC) is the tenth most commonly diagnosed cancer. High recurrence, chemoresistance, and low response rate hinder the effective treatment of BC. Hence, a novel therapeutic strategy in the clinical management of BC is urgently needed. Medicarpin (MED), an isoflavone from Dalbergia odorifera, can promote bone mass gain and kill tumor cells, but its anti-BC effect remains obscure. This study reve aled that MED effectively inhibited the proliferation and arrested the cell cycle at the G1 phase of BC cell lines T24 and EJ-1 in vitro. In addition, MED could significantly suppress the tumor growth of BC cells in vivo. Mechanically, MED induced cell apoptosis by upregulating pro-apoptotic proteins BAK1, Bcl2-L-11, and caspase-3. Our data suggest that MED suppresses BC cell growth in vitro and in vivo via regulating mitochondria-mediated intrinsic apoptotic pathways, which can serve as a promising candidate for BC therapy.